Leverage’–An Analysis and its Impact on Profitability with Reference to Selected Oil and Gas Companies in India - Priyanka Dineshgiri Meghanathi; Alok Kumar Chakrawal (Newinera Publisher, 2022)
Oil and gas sector is among the eight core industries in India and plays a key role in influencing decision making for all the other important sectors of the economy. The main objective of the study is to examine and evaluate the impact of leverage on profitability with reference to oil and gas companies in India. For that researcher has been selected top five companies like Reliance Industries Ltd (RIL), Oil and Natural Gas Corporation (ONGC), Indian Oil Corporation Ltd (IOCL), Bharat Petroleum Corporation Ltd (BPCL), and Gas Authority of India Ltd (GAIL) based on market capitalisation. Secondary data have been used during the study period 2016-17 to 2020-21. For analyzing the leverage and profitability position the researcher have been taken financial leverage as independent variable and earning per share as dependent variable. For testing hypothesis some statistical tools and techniques like one way ANOVA, correlation and regression have been used by researcher. The major findings of ANOVA indicated that there in significant difference in financial leverage and earning per share of selected oil and gas companies during the study period. Correlation results showed that there is positive correlation between financial leverage with eps in reliance but in all other company’s financial leverage is negatively related with eps. Regression analysis found that there is no significant impact of financial leverage on eps in RIL, ONGC and IOCL but in BPCL and GAIL financial leverage has significant impact on EPS.